Polygyny, Inequality, and Social Unrest - Tim Krieger; Laura Renner (ZBW - Leibniz Information Centre for Economics, 2021)
This paper proposes three theoretical mechanisms through which polygyny may be related to social unrest. The mechanisms are related to different dimensions of grievance-inducing and, partly, greed-related inequality, which may occur in polygynous societies. These dimensions include (i) economic, reproductive and social inequality resulting in relative deprivation among non-elite men; (ii) inequality within elites when it comes to the distribution of resources and inheritance, both related to the relative position of dependent family members in a clan; and (iii) gender inequality in general. Using data for 41 African countries from 1990-2014, we provide evidence for these mechanisms and their relationship to social unrest. We find that especially the first and third dimension of inequality are correlated with social unrest. Furthermore, we consider several potential counter-arguments but do not find support for them.
Keywords: D74; J12; J16; 330; polygyny; inequality; women's rights; social unrest; Africa; institutions